Electroactive polyoxometalate-based molecular layers for nano-electronics - Salles, Raphael (Nanyang Technological University, 2022)
Polyoxometalates (POMs) are nano-scaled metal-oxides, considered as promising candidates in many application fields thanks to their electron reservoir and redox properties. When turned into hybrids, by adding at least one organic arm, POMs can be used as platforms for the synthesis of larger devices. This thesis, realized in co-tutelle between Sorbonne Université and Nanyang Technological University, presents the results of this PhD work focusing on two aspects of POMs-based hybrids integration in large systems for different applications. Firstly, the formation of auto-assembled discrete species and their aggregation under specific solvent conditions was investigated. While on one hand a gel was obtained (organo- or hydro-), on the other hand square-shaped structure were obtained, leading to vesicles or elongated cherry-branches according to the solvent. Secondly, the covalent grafting of POM-based hybrids on ITO substrates for the formation of memory devices was studied. After confirmation of the thickness and the characteristics of the grafted layer via a panel of techniques (SEM, AFM, XPS…), a top electrode was deposited to measure the memory properties of the final system. It confirmed the resistive memory nature, the non-volatility of the device and the “write once read many” character, where an information can be stored but not erased.